The Legal Regulation of One-Person Company as a New Legal Approach in the Saudi Economy - Awad , Hani Mohamed Mounes (Dirasat: Shari’a and Law Sciences, 2020)
The present study examines the legal system of a one-person company in Saudi law; this system is considered as a new legal approach in the Saudi economy. Under the new Commercial Companies Law of 2015, the Saudi legislator ratified for one person (natural or legal), the establishment of a company in two forms: the Limited Liability Partnership Company and Joint Stock Company. The adoption of the Saudi legislator for the legal system of a one person is in line with the vision the Kingdom of Saudi Arabia that aims to engage the private sector in the national economy due to it is role as main supporter. The ratification for the establish of a one-person company is considered as a strong incentive for the business sector for a number of reasons such as the determination of the responsibility of the partner by monitoring the capital of the company without exceeding its liability for its debts for the personal finance. The establishment of a one-person company is considered as an exception to the principle that reflected in Article 2 of the Companies Law. The study investigates the nature of the one-person company besides its distinctive characteristics and economic importance, which makes the Saudi legislator to ratify the establishment of the two forms companies on the exceptional legal bases. Finally, the study reveals the means of establishing a one-person company and the mechanisms of its management.